Effects of Tetracycline and Temperature on Drosophila melanogaster Infected with Wolbachia Inducing the Popcorn-Effect - ENDANG SRIMURNI KUSMINTARSIH (Indonesian Society for microbiology, 2012)
The expression of cytoplasmic incompatibility, parthenogenesis, and feminization in many hosts of Wolbachia is influenced by environmental factors such as temperature and antibiotics. Therefore, it might also affect Wolbachia inducing popcorn-effect. To examine the effects of temperature and antibiotic treatment on the life span of Drosophila melanogaster harbouring the popcorn-effect inducing strain of Wolbachia, flies were reared in different temperature such as at 20 and 29 °C, and cultured (from egg to adult stage) on a medium containing tetracycline. The tetracycline-treated Wolbachia was established by placing 0.25 mg m L-1 of tetracycline in the media. The result showed that there was no difference in the life span of D. melanogaster infected with Wolbachia popcorn-effect under untreated and treated condition with tetracycline at 20 °C. Therefore, there is no popcorn-effect in the D. melanogaster at low temperature (20 °C). While the life span of D. melanogaster at 29 °C, where infected flies have a shorter life span than treated flies. Popcorn-effect (shorter life span) was found at 29 °C.